Recombination and DNA Repair in Helicobacter pylori - Dorer, Marion S. (2011)
All organisms have pathways that repair the genome, ensuring their survival and that of their progeny. But these pathways also serve to diversify the genome, causing changes on the level of nucleotide, whole gene, and genome structure. Sequencing of bacteria has revealed wide allelic diversity and differences in gene content within the same species, highlighting the importance of understanding pathways of recombination and DNA repair. The human stomach pathogen Helicobacter pylori is an excellent model system for studying these pathways. H. pylori harbors major recombination and repair pathways and is naturally competent, facilitating its ability to diversify its genome. Elucidation of DNA recombination, repair, and diversification programs in this pathogen will reveal connections between these pathways and their importance to infection.